Introduction to the digital format of the Philippine printing industry-an impact analysis and strategic prospective - Mercado, Rogel De Villa (Quezon City University of the Philippines Diliman, 2009)
This project, "Introduction to the Digital Format of the Philippine Printing Industry-An Impact Analysis and Strategic Prospective", is a technology management paper focused on the dynamics-innovation, diffusion and adoption-of the digital technologies with the printing industry. This paper looks into the current situation of the Philippine Printing Industry and its adoption of the digital technologies. It aims to analyze and assess the impact of the digital technologies to the local industry and to provide recommendations or strategic prospective to be competitive. The first chapter is the introduction of the paper. It discusses the background, significance and the objectives of this project. It establishes the rationale on why the project is undertaken and the beneficiaries of the results of the project. The conceptual framework is discussed on the second chapter. The input-transformation-output framework will be used in understanding the current state of the Philippine Printing Industry and analyzing the impact of the digital technology to this framework. Technology management theories and concepts incorporated such as innovation, diffusion, adoption and acquisition of technology are also discussed in this chapter. The third chapter lengthily discusses the methodology employed by the proponent in executing the project. This chapter elaborates the research type, required data and the tools that will be used by the proponent. The proponent explains in this chapter the exploratory and predictive nature of this research being a pioneer in this topic. The sources of data are also outlined- the interview as the primary data and government statistical data, available studies and other literature as secondary data. Technology management concepts of innovation, diffusion and adoption and hierarchy of firm level technological capability are used as tools by the proponent on understanding the technological dynamics of digital technology in the printing industry.
The fourth chapter presents the review of related studies. In this chapter, the proponent defines and compares the analog and digital technologies as well as their advantages and disadvantages. The chapter also highlights the emerging trends of the digital printing market-the new products and services offered. It also provides the new business models for digital printing which are becoming prevalent. An important part of this chapter is the lessons learned on the successful digital printing firms in the United States. Using the different case studies of digital printing firms in the US, the proponent will utilize the learning in giving strategic recommendations for competitiveness. The case studies also reveal the inherent importance of exploiting and managing technology for firm's success. The fifth chapter extensively presents the data gathered and analysis. It started with the overview of the Philippine printing industry. The first section provides the scope of the industry. This is followed by the current industry structure detailing the firms, suppliers, customers, legal and regulatory framework and industry associations. The succeeding section uses the conceptual framework-input-transformation-output-in explaining the state of the local printing industry. The proponent relies on the national statistical data on presenting and analyzing the data for the different components of the framework. The last section summarizes the interview with the president of the industry association selected by the proponent. It gives light on the digital technology of the printing industry in the country and his perspective and recommendations. Based on all the related studies and data gathered and analyzed, the proponent extensively presents the findings and discussions in the sixth chapter. The proponent explains the innovation in digital technology as a product of both technology push and market pull. The proponent likewise used the S-curve in discussing the technology maturation characterized by the digital and analog printing technologies. He finds that analog is already in the aging period while digital is in its rapid growth stage. Also, the adoption of digital technology is rapid in the United States evidenced by innovators and early adopter firms. The Philippine printing firms are characterized by being late adopters and laggards evidenced by very slow adoption. The proponent gives light on the factors affecting the adoption of the digital technologies in the Philippines. Using the S-Curve, the proponent likewise plotted the curves for digital and analog/traditional printing technologies. He finds that digital methods are outpacing the analog/traditional method. Based on the data gathered and analyzed, the Philippine printing industry is on the analog S-curve reaching its maturation/aging stage with very limited or almost no growth. The last (seventh) chapter provides the recommendations and strategic prospective of the proponent based on the foregoing. He recommends implementing three different technological development models of linear approach, leapfrogging approach and niche approach in coping up and superseding competition. He highlights the importance of technological learning and innovation in the local printing firms. He stresses technology management which includes the competitive strategy to uplift the situation of the Philippine printing industry. The proponent also suggests the following actions for the industry : 1. Assess and develop the demand for digital printing market. 2. Strategize ways in increasing in resources. 3. Invest and exploit new and enabling technologies. 4. Think global. 5. Develop capability, skills and competence of human resources in digital technologies. 6. Create the supporting infrastructure. 7. Technological learning, scanning and intelligence. 8. Collaboration and linkages with stakeholders. 9. Government initiatives. In closing the proponent recommends further and more comprehensive studies on the topic which are not accomplished because of resource and time constraints.
In partial fulfillment of the requirements in TM 299.2
Thesis
Keywords: Printing industry -- Management -- Philippines; Economic impact analysis; Business planning